Influence of pack boriding on the wear and corrosion resistance of AISI H13 steel - Heck, S. C. (2016)
This work investigates the effect of pack boriding time and temperature on the wear and corrosion resistance of AISI H13 tool steel. Steel samples were pack borided at 900 and 1000ºC for periods of 2 and 4 h; followed by non-abrasive fixed-ball microwear tests on borided and non-borided samples. The corrosion resistance was evaluated by potentiodynamic polarization tests in HCl 0.1 M. High hardness layers were formed on the samples for all treatment conditions employed. The layer's properties, such as hardness, thickness, layer/substrate interface morphology, and phases formed, were influenced by steel composition. For AISI H13 steel, which has a larger amount of alloying elements than carbon steel, the formed layers were hard, thin, with a smoother interface. For all treatment conditions, the presence of Fe2B, FeB, and CrB were identified. The wear and corrosion resistance of borided samples was significantly increased. The best results were obtained for samples borided at 1000ºC.